CONTROLLING COMFORTNESS OF BIG PRODUCTION BUILDINGS IN TROPICAL REGION FACTORIES BY PROPER FAN ARRANGEMENT - Rudi Irawan; Dena Hendriana (Asosiasi Dosen Muda Indonesia, 2022)
A production building is one of important buildings in a factory. A lot of factories in Indonesia are still considered labor intensive factories. People need a convenient place to work to produce quality products. A discomfort workspace condition for workers often causes not only poor productivity but also poor quality of product. Therefore, it is important to create healthy working environment for workers. Air comfort is determined at least by five factors that are temperature, relative humidity, oxygen content, air pressure and air flow. Common working space in a production building is a huge space, so it is almost impossible to apply air conditioner system to such a big space due to too high investment cost and operational cost and economically unfeasible. In tropical region, oxygen content, air pressure and air flow can be controlled by letting the fresh air from outside to enter the building. Air movement will also lower temperature sensation on human skin. Commonly in factories, the managements equip the factories with fans to improve air comfort in the production building. However, this current research found that improper fan system configuration and direction does not help to improve air comfort and even worsens the air condition because the air movement blown from improper fan configuration and direction can cancel each other and trap the heated air recirculated inside the building. This research found that arranging the fans in one direction will poster air movement from one end to the other end of building as well as keep the fresh air entering building from one side and the used air exiting the building through the other side. Because a fan is not a cooling device, the air temperature inside the building similar to that of fresh air, but the air movement pushed by the fans will reduce temperature sensation on human around 2 0C.